Prioritizing conservation areas to mitigate connectivity loss and local extinction risk of a small carnivore (Leopardus guttulus) in South America - Sartor, CC; Cushman, SA; Wan, HY; Tirelli, FP; Althoff, SL; Eizirik, E; Trigo, TC; de Freitas, TRO (Springer, 2024)
Effective conservation management depends on the maintenance of key areas that allow population connectivity across the landscape. However, the lack of knowledge of how habitat conversion affects species movement hinders the identification of these areas. Here, we analyzed the impact of habitat fragmentation on landscape connectivity for Leopardus guttulus, a small Neotropical felid threatened by the high habitat fragmentation across the Atlantic Forest, and mapped and ranked the most important core areas and corridors for conservation actions. We also estimated genetic diversity indices and predicted the viability of the current core areas in the future. Our analyses suggest that L. guttulus populations are fragmented, and connectivity links between populations are few and weak. We predict that due to their size, estimated density and low connectivity, some current core areas may not maintain viable populations in the long-term. Also, ongoing land-use changes may further isolate remaining populations, leading to progressive reductions in the populations they support. In this study, we spatially prioritize the most critical areas for L. guttulus conservation and highlighted the urge that exists in the adoption of management measures for its conservation.